Alcances para una respuesta jurídica integral al comercio ilegal de oro - Valverde Luna, Vanessa Sofía; Collantes Añaños, Diego Alonso (Pontificia Universidad Católica del Perú, 2017)
This paper pretends to analyze the functioning and the limitations of some legal tools that the Peruvian state has posed as a part of his normative answer to the grave phenomenon of illegal gold mining, organized form of criminality whose utilities have surpassed the ones of drug trafficking. With this purpose, two axes of analysis has been proposed with incidence upon the illegal commercialization of gold: (i) the criminal tools, which specifically involve the crimes of illegal mining, clandestine commerce and money laundering; and (ii) the administrative tools, which involve the Legislative Decrees N° 1103 and 1107, the Supreme Decrees N° 012-2012-EM and N° 17-2009-MTC, among others. The authors have noticed several legislative policy errors in these elements and therefore implement recommendations to increase the global effectiveness of the regulation.

El presente trabajo apunta a evaluar el funcionamiento y las limitaciones de algunas de las herramientas jurídicas que el Estado peruano ha planteado como parte de su respuesta normativa frente al grave fenómeno de la minería ilegal, forma organizada de criminalidad cuyas ganancias ilícitas han superado en los últimos años a las del tráfico ilícito de drogas. Con tal finalidad, se han propuesto dos ejes de análisis con incidencia en la comercialización del oro ilegal: (i) las herramientas penales, que específicamente comprenden los delitos de minería ilegal, comercio clandestino y lavado de activos; y (ii) las herramientas administrativas, compuestas por los Decretos Legislativos No. 1103 y 1107, los Decretos Supremos No. 012-2012-EM y No. 17-2009-MTC, entre otros. Los autores han advertido diversos errores de política legislativa en estos elementos e implementan recomendaciones para incrementar la eficacia global de la regulación.
Approaches for a comprehensive regulatory response to illegal gold commerce
Keywords: Minería Ilegal; Comercialización de Oro; Comercio Clandestino; Lavado de Activos; Rutas Fiscales; Transporte Terrestre de Valores; Adquirente de Oro; Formalización de la Pequeña Minería y Minería Artesanal; https://purl.org/pe-repo/ocde/ford#5.05.00